REVOLUSI INFORMASI KARIER DI ERA DIGITAL: STUDI KASUS KONTEN TIKTOK @vmuliana - Azahra, Khanisa; Suparman (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study aims to determine the effect of exposure intensity of TikTok content @vmuliana on Followers' fulfillment of information needs related to the world of work. The research used a quantitative explanatory method. Data were obtained through an online questionnaire distributed to 100 respondents aged 18–34 years who follow the TikTok account @vmuliana. The independent variable in this study is the intensity of exposure, which includes frequency, duration, and attention. The dependent variable is the fulfillment of information needs, measured using four approaches: current need, everyday need, exhaustive need, and catching up need. Data analysis was conducted using a simple linear regression test with SPSS. The results show that there is a significant influence between exposure intensity and the fulfillment of information needs. These findings confirm that the more intense the exposure to educational content, the higher the likelihood that the audience's information needs are fulfilled.